Privacy in view of telemedicine: Contributions of the philosophy of technology to bioethics - Álvarez Díaz, Jorge Alberto (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The philosophy of technology is a recent branch of philosophy in general. It can provide tools for problems arising from recent technological applications, such as telemedicine. A problem repeatedly pointed out by bioethics is privacy in general, and the changes that can be introduced by the increasing use of technology. Commenting on proposals from the World Medical Association and contemporary data derived from the COVID-19 pandemic, it can be recognized that privacy is an ethical requirement that requires regulation through its political implementation for its adequate legal protection.